Nilai Inti Universitas Katolik di Indonesia: Pengembangan Budaya Organisasi Berdasarkan Moral Exemplars - Mikhael Dua (Respons: Jurnal Etika Sosial, 2019)
To develop organizational culture in Catholic universities in Indonesia by applying core values raises the question of its eff ectiveness. Departing from Richard P. Nielson’s theory of cultural learning action and phenomenological refl ection on the results of the Focus Group Discussion (FGD) and KII this article explains that the organizational culture of Catholic university in Indonesia is based on a Catholic spirituality which is supported by hierarchical leadership. Th e development of an organizational culture that relies on the participation of community members still relies on such hierarchical leadership as moral exemplars.